Ribociclib plus endocrine therapy for premenopausal women with hormone-receptor-positive, advanced breast cancer (MONALEESA-7): a randomised phase 3 trial. Issue 7 (July 2018) - Tripathy, Debu; Im, Seock-Ah; Colleoni, Marco; Franke, Fabio; Bardia, Aditya; Harbeck, Nadia; Hurvitz, Sara A; Chow, Louis; Sohn, Joohyuk; Lee, Keun Seok; Campos-Gomez, Saul; Villanueva Vazquez, Rafael; et al.
Summary: Background: In MONALEESA-2, ribociclib plus letrozole showed improved progression-free survival compared with letrozole alone as first-line treatment for postmenopausal patients with hormone receptor (HR)-positive, HER2-negative, advanced breast cancer. MONALEESA-7 aimed to assess the efficacy and safety of ribociclib plus endocrine therapy in premenopausal women with advanced, HR-positive breast cancer. Methods: This phase 3, randomised, double-blind, placebo-controlled trial was done at 188 centres in 30 countries. Eligible patients were premenopausal women aged 18–59 years who had histologically or cytologically confirmed HR-positive, HER2-negative, advanced breast cancer; an Eastern Cooperative Oncology Group performance status of 0 or 1; measurable disease as per Response Evaluation Criteria in Solid Tumors version 1.1 criteria, or at least one predominantly lytic bone lesion; and had not received previous treatment with cyclin-dependent kinases 4 and 6 inhibitors. Endocrine therapy and chemotherapy in the adjuvant or neoadjuvant setting was permitted, as was up to one line of chemotherapy for advanced disease. Patients were randomly assigned (1:1) via interactive response technology to receive oral ribociclib (600 mg/day on a 3-weeks-on, 1-week-off schedule) or matching placebo with either oral tamoxifen (20 mg daily) or a non-steroidal aromatase inhibitor (letrozole 2·5 mg or anastrozole 1 mg, both oral, daily), all with goserelin (3·6 mg administered subcutaneously on day 1 of every 28-day cycle). Patients and investigators were masked to treatment assignment. Efficacy analyses were by intention to treat, and safety was assessed in all patients who received at least one dose of any study treatment. The primary endpoint was investigator-assessed progression-free survival. MONALEESA-7 is registered withClinicalTrials.gov, NCT02278120 and is ongoing, but no longer enrolling patients. Findings: Between Dec 17, 2014, and Aug 1, 2016, 672 patients were randomly assigned: 335 to the ribociclib group and 337 to the placebo group. Per investigator's assessment, median progression-free survival was 23·8 months (95% CI 19·2–not reached) in the ribociclib group compared with 13·0 months (11·0–16·4) in the placebo group (hazard ratio 0·55, 95% CI 0·44–0·69; p<0·0001). Grade 3 or 4 adverse events reported in more than 10% of patients in either group were neutropenia (203 [61%] of 335 patients in the ribociclib group and 12 [4%] of 337 in the placebo group) and leucopenia (48 [14%] and four [1%]). Serious adverse events occurred in 60 (18%) of 335 patients in the ribociclib group and 39 (12%) of 337 in the placebo group, of which 15 (4%) and six (2%), respectively, were attributed to the study regimen. 12 (4%) of 335 patients in the ribociclib group and ten (3%) of 337 in the placebo group discontinued treatment because of adverse events. No treatment-related deaths occurred. 11 deaths occurred (five [1%] in the ribociclib group and six [2%] in the placebo group) during or within 30 days after treatment, most of which were due to progression of the underlying breast cancer (three [1%] and six [2%]). The remaining two deaths in the ribociclib group were due to an intracranial haemorrhage in an anticoagulated patient, and a pre-existing wound haemorrhage in another patient. Interpretation: Ribociclib plus endocrine therapy improved progression-free survival compared with placebo plus endocrine therapy, and had a manageable safety profile in patients with premenopausal, HR-positive, HER2-negative, advanced breast cancer. The combination could represent a new first-line treatment option for these patients. Funding: Novartis.